2017
DOI: 10.1007/s00210-017-1375-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of ceramide de novo biosynthesis rescue damages induced by cigarette smoke in airways epithelia

Abstract: Exposure to cigarette smoke represents the most important risk factor for the development of chronic obstructive pulmonary disease (COPD). COPD is characterized by chronic inflammation of the airways, imbalance of proteolytic activity resulting in the destruction of lung parenchyma, alveolar hypoxia, oxidative stress, and apoptosis. Sphingolipids are structural membrane components whose metabolism is altered during stress. Known as apoptosis and inflammation inducer, the sphingolipid ceramide was found to accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…For these reasons, immortalized human bronchial epithelial (HBE) cells are widely used and established as experimental models to study lung diseases [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Cellular Models Of Bronchial Epithelium Exposed To Cse: Prim...mentioning
confidence: 99%
“…For these reasons, immortalized human bronchial epithelial (HBE) cells are widely used and established as experimental models to study lung diseases [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Cellular Models Of Bronchial Epithelium Exposed To Cse: Prim...mentioning
confidence: 99%
“…Very recently, Bodas et al showed that Cer/Sph ratio was elevated in COPD subjects as well as in mice exposed to cigarette smoke, worsening COPD-emphysema severity [98]. Excessive Cer content triggers damages of structural airway epithelial cells [99][100][101], which is involved in pulmonary tissue destruction [102] and contributes to maintain pulmonary inflammation [103].…”
Section: Spl Metabolism and Copdmentioning
confidence: 99%
“…It has already been demonstrated in different diseases that Cer plays a pro-inflammatory role in, for instance, airway inflammation, pulmonary edema, inflammatory bowel disease, inflammation during labor, post myocardium ischemic and cystic fibrosis [159][160][161][162][163][164][165][166][167][168]. But, the role of SLs in microglia was depicted only a few years ago when Jung and colleagues [162] showed that Cer with acyl chain length C2 to C8 was able to block the inflammation induced by LPS.…”
Section: Microglia and Sls Activation In Brain Tumormentioning
confidence: 99%